Do company performance, multinational company and audit fee affect audit delay? - Muhammad Diffon Leditho; Widyahayu Warmmeswara Kusumastati; Muhamad Safiq (JAAF (Journal of Applied Accounting and Finance), 2023)
This study aims to analyze the effect of several variables on audit delay. Those variables are profitability, solvability, multinational company, and audit fee. The population of this study was 70 companies listed on Indonesia Stock Exchange from 2016 to 2020 which late in publishing annual report. The sampling method used is the purposive sampling method. It was obtained 30 companies for five years of observation with 147 data. The results of this study indicate that profitability has no negative effect on audit delay, solvency has a negative effect on audit delay, multinational companies have no negative effect on audit delay, audit fee has a negative effect on audit delay. It means that investors should be aware on company with high solvability and audit fee, as a sign of audit delay.